Emergency Profile of Pediatric Patients Based on Pediatric Early Warning Score in the Emergency Department of the Adam Malik Hospital - Danau Arta, Grace; Malisie, Ririe Fachrina; Wahyuni, Arlinda Sari; Prapiska, Fauriski Febrian; Siregar, Irma Sepala Sari (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2024)
Background: High morbidity and mortality rates in pediatric patients indicate the necessity of a Pediatric Early Warning Score (PEWS) capable of early clinical deterioration identification and providing an opportunity for healthcare professionals to promptly manage patients. This study aimed to serve as foundational data and as an evaluative tool to enhance the proficiency of healthcare workers in assessing patient deterioration. Methods: This study utilized a descriptive method with a cross-sectional design and consecutive sampling technique who were treated from January to December 2022.   Results: there were 119 samples, the majority of gender was male (54.6%), the majority of the age group was 1-4 years old (37.8%), and the majority of the disease group was infection (31.1%). Both male and female majority had green PEWS (54.6%) and (45.4%), the majority of patients with an age range of 1 month to 5 years had red PEWS, the majority of infectious disease group had green PEWS, and the majority of patients with green PEWS had discharge outcome.   Conclusion: This study provides an overview of characteristics in pediatric patients and shows the majority of pediatric emergency department patients come with non-emergency conditions.